User-cooperative dynamic resource allocation for backscatter-aided wireless-powered MEC network - Huaiwen He; Chenghao Zhou; Feng Huang; Hong Shen; Yihong Yang; Shangsong Liang; Xinyuan Jin (Scientific Reports)
Abstract Backscatter communication, which transmits information by passively reflecting radio frequency (RF) signals, has become a focal point of interest due to its potential to significantly enhance the energy efficiency of Wireless Power (WPMEC) networks and extend the operational lifespan of terminal devices. However, there is little research on the integration of user cooperation in WPMEC scenarios within volatile network environments. In this paper, we propose a dynamic task offloading algorithm for a Backscatter-assisted WPMEC system, which involves two (MDs) and a Hybrid Access Point (HAP) with user cooperation. We formulate the energy efficiency (EE) maximization problem as a stochastic programming problem, considering the randomness of task arrivals and time-varying wireless channels. By leveraging Dinkelbach’s method and stochastic network optimization technique, we transform the problem into a series of deterministic sub-problems for each time slot, and convert the non-convex sub-problem into convex ones. We propose a low-complex EE maximization algorithm to solve the convex problems efficiently. We conduct extensive simulations to validate the performance of our algorithm under various system parameter settings. Experimental results demonstrate that our algorithm not only outperforms the benchmark algorithms by approximately 23%, but also stabilize all queues within the MEC system.